2003
DOI: 10.1038/nature01871
|View full text |Cite
|
Sign up to set email alerts
|

Extreme reversed sexual size dimorphism in the extinct New Zealand moa Dinornis

Abstract: The ratite moa (Aves; Dinornithiformes) were massive graviportal browsers weighing up to 250 kg (ref. 1) that dominated the New Zealand biota until their extinction approximately 500 yr ago. Despite an extensive Quaternary fossil record, moa taxonomy remains problematic and currently 11 species are recognized. Three Dinornis species were found throughout New Zealand and differed markedly in size (1-2 m height at back) and mass (from approximately 34 to 242 kg). Surprisingly, ancient mitochondrial DNA sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 13 publications
2
130
0
1
Order By: Relevance
“…However, since Holdaway's (1994) phylogeny did not recover monophyly of Aquilini, the Harpagornis-Aquila relationship also seems doubtful and molecular verification would be desirable. Using ancient DNA, this might be possible given that extensive molecular sequences have been obtained from various sub-fossil moa species of approximately the same age (Bunce et al, 2003;Huynen et al, 2003).…”
Section: Biogeographymentioning
confidence: 99%
“…However, since Holdaway's (1994) phylogeny did not recover monophyly of Aquilini, the Harpagornis-Aquila relationship also seems doubtful and molecular verification would be desirable. Using ancient DNA, this might be possible given that extensive molecular sequences have been obtained from various sub-fossil moa species of approximately the same age (Bunce et al, 2003;Huynen et al, 2003).…”
Section: Biogeographymentioning
confidence: 99%
“…As is the case for most extinct taxa, little is known about their biology except some insights into their feeding habits, gained from their gut contents and genetic and morphological analyses of coprolites (e.g., Burrows et al, 1981;Burrows, 1989;Wood et al, 2008Wood et al, , 2013. It has also been demonstrated that moa displayed reverse sexual dimorphism with the females being up to 280% heavier than the males (Bunce et al, 2003;Huynen et al, 2003). Moreover, Allentoft et al (2010) demonstrated by a molecular sexing technique that there was an overall 5:1 excess of females among 267 individuals sampled in North Canterbury.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA was then isolated and purified using Qiagen (Valencia, CA, USA) silica spin columns. A mtDNA control region sequence of 340 bp (excluding primers) was amplified from 87 individuals using two sets of overlapping primers (Bunce et al, 2003). The associated GenBank accession numbers for the individual mtDNA sequences are presented in Allentoft et al (2014).…”
Section: Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) We can reject the possibility of failed extraction on the grounds that (i) the technique allows the recovery of host DNA from the samples, (ii) DNA sequences presumably derived from environmental bacteria are recovered from the samples and (iii) because this extraction technique, or a related version, has been used in a wide variety of published studies, including samples with marginal survival of bacterial, fungal and vertebrate DNA (Baron et al 1996;Barnes et al 2002;Bunce et al 2004;Shapiro et al 2004;Willerslev et al 2004).…”
Section: (Tpp15-l171 (Gcgttctgcccttttgacgttg)/h86 (Ccgactgctcagcccactmentioning
confidence: 99%